Prevalence, Intensity, and Risk Factors for Helminth Infections in Pigs in Menoua, Western Highlands of Cameroon, with Some Data on Protozoa - Marc K. Kouam; Fabrice D. Ngueguim (Journal of Parasitology Research)
Helminthes affect satisfactory pig farming by causing poor growth rate and infertility. The objective of this study was to investigate the occurrence of helminthes in pig production, as well as factors influencing their prevalence in Menoua, Western Highlands of Cameroon. Thus, 597 fecal samples from 100 farms of three production types (farrower, grower, and farrow-to-finish) were collected together with data on farmer and management characteristics. Samples were qualitatively and quantitatively analyzed. Eggs of eight helminthes were identified: Hyostrongylus rubidus (81.10%, 50-550 epg), Strongyloides ransomi (34.5%, 50-150 epg), Trichostrongylus sp. (28.1%, 50-650 epg), Ascaris suum (11.6%, 50-200 epg), Metastrongylus sp. (10.4%, 50-250 epg), Oesophagostomum dentatum (5.7%, 50-150 epg), Trichuris suis (4.0%, 50-150 epg), and Macracanthorhynchus hirudinaceus (0.2%, 50-50 epg). The overall prevalence was 89.3% (533 out of 597). Single infestations were 30.2%, while mixed infestations were 59.1%. A. suum, S. ransomi, and strongyles (H. rubidus, Trichostrongylus sp., Metastrongylus sp., and O. dentatum) were found in almost all age groups but the prevalence of A. suum increased with the growing age to drop in older animals. H. rubidus was found in all farm types followed by S. ransomi in farrower and farrow-to-finish farms. The other parasites were present only in farrow-to-finish farms. Coccidia parasites were also found including Isospora suis (26.30%, 50-12500 oocysts per gram of feces (opg)) and Eimeria spp. (1.40%, 100-100 opg). The risk of infestation for some parasites was lower with increasing herd size, high education level of farmers, and in wooden piggeries and semipermanent structures. The infestation risk was higher for all the investigated parasites for pigs escaping the pens. The overall significance of these parasites on growth and reproduction of the naturally infested pigs deserve assessment. Necropsy studies to confirm the worm burden are needed. Risk factors were identified, thus paving the way to design successful helminth control in pig production enterprises.